After Megalopolis - Rappaport, Alexander (project baikal, 2014)
In the article the concepts of city and urban way of life are critically reexamined in the wake of megapolitan crisis and global communications. The concept of city is still and ignoring rediscovery of alienation and meaning of identity limits in consuming oriented society. In 21 century understanding of urban and planetary phenomena should be reassessed and the fundamental limits of telluric destiny of the humankind rediscovered as a next step in architectural approach to survival of mankind. There are some special points emphasizing situationist approach to urban and architectural theory.
Keywords: city; urbanism; utopia; heterotopias; atopia; situationism; planetary claustrophobia; alienation; identity; design